Mobilizing for democracy : citizen action and the politics of public participation - Coelho, Vera Schattan P.; Von Lieres, Bettina (London : Zed Books, 2010)
Using new empirical case studies from around the world, this book illustrates how alternative forms of political mobilization - protests, social participation, activism, litigation & lobbying - engage with the formal institutions of representative democracy in ways that constitute the very essence of democratic politics.
Includes bibliographical references and index.
Keywords: Political participation -- Case studies; Democracy -- Case studies